Student feedback: a learning and teaching performance indicator. Issue 4 (7th September 2015) - Barry O'Mahoney, Prof.; Kinash, Shelley; Naidu, Vishen; Knight, Diana; Judd, Madelaine-Marie; Nair, Chenicheri Sid; Booth, Sara; Fleming, Julie; Santhanam, Elizabeth; Tucker, Beatrice; Tulloch, Marian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The paper aims to disseminate solutions to common problems in student evaluation processes. It proposes that student evaluation can be applied to quality assurance and improving learning and teaching. The paper presents solutions in the areas of: presenting outcomes as performance indicators, constructing appropriate surveys, improving response rates, reporting student feedback to students and student engagement as a feature of university quality assurance. Design/methodology/approach – The research approach of this paper is comparative case study, allowing in-depth exploration of multiple perspectives and practices at seven Australian universities. Process and outcome data were rigorously collected, analysed, compared and contrasted. Findings – The paper provides empirical evidence for student evaluation as an instrument of learning and teaching data analysis for quality improvement. It suggests that collecting data about student engagement and the student experience will yield more useful data about student learning. Furthermore, findings indicate that students benefit from more authentic inclusion in the evaluation process and outcomes. Research limitations/implications – Because of the chosen research approach, the research results may lack generalisability. Therefore, researchers are encouraged to test the proposed propositions further and apply to their own university contexts. Practical implications – The paper includes recommendations at the institution- and sector-wide levels to effectively use student evaluation as a university performance indicator and as a tool of change. Originality/value – This paper fulfils an identified need to examine student evaluation processes across institutions and focuses on the role of student evaluation in quality assurance.